2004
DOI: 10.1074/jbc.m410317200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase 4 Is a Positive Regulator of Hematopoietic Progenitor Kinase 1

Abstract: Hematopoietic progenitor kinase 1 (HPK1) is a hematopoietic specific mammalian Ste20-like protein kinase and has been implicated in many cellular signaling pathways including T cell receptor (TCR) signaling. However, little is known about the in vivo regulation of HPK1. We present evidence that HPK1 is positively regulated by protein phosphatase 4 (PP4; also called PPX and PPP4), a serine/threonine phosphatase. We found that PP4 interacted with HPK1 and that the proline-rich region of HPK1 was necessary and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 79 publications
1
23
0
1
Order By: Relevance
“…In vitro PP5 can dephosphorylate Thr845, an activation-associated site on ASK1. These findings suggest that PP5 functions to inactivate ASK1 and perhaps other MAP3Ks (Zhou et al, 2004).…”
Section: Phosphatasesmentioning
confidence: 88%
“…In vitro PP5 can dephosphorylate Thr845, an activation-associated site on ASK1. These findings suggest that PP5 functions to inactivate ASK1 and perhaps other MAP3Ks (Zhou et al, 2004).…”
Section: Phosphatasesmentioning
confidence: 88%
“…In addition, the characterization of PP4-interacting proteins during pre-TCR or TCR signaling may further elucidate the functional roles of PP4 in T-cell development, apoptosis, and activation. Specifically, our previous studies have demonstrated that PP4 interacts with, dephosphorylates, and activates HPK1 (30), an upstream kinase known to regulate T-cell activation and apoptosis (1,20). Moreover, PP4 associates with, dephosphorylates, and inhibits histone deacetylase 3 (29), which was originally cloned from phytohemagglutinin-activated T cells and whose mRNA is upregulated in peripheral blood mononuclear cells cultured with anti-CD3 antibody (3).…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, Pph3, but not Pph22, dephosphorylates ␥H2AX, whose posttranslational modification is an early hallmark following a double-strand break (15). PP4 interacts with and regulates HPK1, a mitogen-activated protein kinase upstream regulator, in a T-cell receptor (TCR)-dependent manner (30), indicating that PP4 may be a novel serine/threonine phosphatase involved in T-cell signaling. By conditional inactivation of PP4 in the T-cell lineage, aberrant thymocyte development, including double-negative 3 stage (DN3) cell arrest and decreased positive selection, was detected.…”
mentioning
confidence: 99%
“…In doing so, it has been suggested that PP4 presumably activates NF-B and facilitates TNF␣-induced activation of JNK kinase (Zhou et al 2002;Mihindukulasuriya et al 2004;Yeh et al 2004;Zhou et al 2004). Since HDAC3 is a regulator of NF-B and of the JNK pathway Zhang et al 2002;Weiss et al 2003), it will be important to elucidate the association of HDAC3 dephosphorylation by PP4 with these signaling pathways in future studies.…”
Section: Discussionmentioning
confidence: 99%